ENGLISH ROMANTICISM AND ITS DEVELOPMENT - O`rmonxonova Zeboxon Xusniddinovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Romanticism, sometimes referred to as the Romantic movement or the Romantic age, was a late eighteenth-century European artistic and philosophical movement. The movement's goal during the Industrial Revolution and the Age of Enlightenment was to promote the value of subjectivity, imagination, and an appreciation of nature in society and culture.